Influence of processing parameters for globular microstructure formation of aluminium 7075 feedstock billet produced by direct thermal method - Megalingam, Arumugampillai; Asnul Hadi, Ahmad; Nasrul Azuan, Alang; Mohd Rashidi, Maarof; Naher, Sumsun
This work aimed to evaluate the processing parameters for forming globular microstructures on billets of aluminium 7075 alloys with a direct thermal method (DTM). Semi-solid metal (SSM) processing is preferred to produce a high-quality product, which reduces casting flaws such as macroscopy, shrinkage, and porosity. It requires a solid globular microstructure in the semisolid aluminium liquid matrix. DTM is a simple SSM technique for creating a globular microstructure in a temperature environment that is typical of nature. In this experiment, molten aluminium 7075 alloys were poured into a cylindrical copper mould at pouring temperatures of 645 °C and 665 °C, then quenched into the water after holding times of 20, 40, and 60 s. Following that, the microstructure of feedstock billets prepared at a range of pouring temperatures and holding times was investigated. Limited information on aluminium 7075 alloy behaviour, and lack of proper understanding of globular microstructure formation are among the problems that arise in this research field. The influence of parameters on DTM processing should be investigated in detail. In particular, there is a lack of information about the aluminium 7075 effects near the liquidus temperature. Therefore, this study investigates the effects of globular microstructure formation and parameters in aluminium 7075 alloys in detail. A uniform high number of spherical primary particles is expected for a globular microstructure. The results of this experiment indicated that a pouring temperature of 665 °C combined with a holding time of 60 s produced a finer and globular microstructure.